Preventive Issues and the Black Elderly: A Biopsychosocial Perspective - Lightfoot, Orlando B. (1983)
Of 26 million black Americans, 8 to 10 percent are elderly. Life expectancy for blacks is on the average 5.5 years less than for whites. Black men on the average live only 64.1 years. Preventive services in an elderly population must focus on maintaining physical health, supporting psychological well-being, and sustaining an adequate economic base and a dependable social-service network. High-risk factors in the elderly include being black, being poor, living alone, experiencing major life changes, being recently bereaved, or being recently discharged from a hospital. Important issues involved in maintaining good psychological and mental health include previous psychological health, previous intellectual capability, and the response to diminished physical health and to other major life changes. An adequate social network must include maintaining or developing friendships, capitalizing on the strengths of subcultural identifications, and having ready access to social, legal, health, and political-action groups.